The use of foot length and foot breadth in estimating standing height of adolescents in Yenagoa, Nigeria - Okumoko, Maureen A.; Akinbami, Felix O.; Peterside, Oliemen; Orimadegun, Adebola E. (International Journal of Contemporary Pediatrics, 2024)
Background: Previous studies have shown that when standing height is difficult to measure, the length of other body parts may be a reliable alternative. However, there is limited information about the use of foot length (FL) and foot breadth (FB) in estimating standing height in the African population. The objective of this study was to investigate the appropriateness of foot length and foot breadth in estimating standing height of adolescents in Yenagoa. Methods: Using a multistage sampling technique, 1222 adolescents were recruited from secondary schools in the Yenagoa local government area. Height, foot length, and foot breadth were measured using standard techniques. Data was analysed and equations for prediction of standing height from foot length and foot breadth, were derived. Results: The mean standing height of the females was significantly lower than that of males (p<0.001). The mean foot length and mean foot breath for males were significantly higher than those for females. The mean foot length and mean foot breadth were found to increase across all the stages of adolescence. There was a significant positive correlation between standing height and foot length (r=0.700; p<0.001), foot breadth (r=0.543; p<0.001), and age (r=0.369; p<0.001). Multiple linear regression was used to derive equations for the estimation of FL and FB. Conclusions: This study found that FL and FB can be used in the estimation of standing height. For adolescents in Yenagoa, the equations derived are recommended for predicting the standing height of those who have difficulty standing upright.